The basic reproductive number for the transmission of four serotypes of dengue model - Pongsumpun, Puntani (My University, 2011)
Dengue disease is transmitted to the human by biting of the infected Aedes Aegypti. This disease is classified as Dengue fever (DF), Dengue hemorrhagic fever (DHF) and Dengue shock syndrome(DSS) depend on the symptom of the patient. There are four serotypes (DEN-1, DEN-2, DEN-3 and DEN-4) of dengue virus. Mathematical model is constructed to describe the transmission of the disease. The severity of the disease depends on the age of the patient. We formulate the mathematical model by dividing the population into juvenile and adult classes. There are the difference transmission probabilities of dengue virus to the juvenile and adult humans for each serotype. We use the standard dynamical modeling method for analyzing this model. The analytical solutions are obtained. The comparisons of the numerical solutions when there are the differences of the basic reproductive numbers are discussed.
Keywords: Basic reproductive number; Dengue disease; Mathematical model; Serotype